1974
DOI: 10.1073/pnas.71.4.1317
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Evidence for the Presence of Two Postaglandin Receptor Sites Regulating the Activity of Intestinal Adenylate Cyclase Sensitive to Escherichia coli Enterotoxin

Abstract: Kinetic behavior most consistent with the presence of two independent, but simultaneously acting, regulatory effector sites for prostaglandins has been presented for adenylate cyclase (EC 4.6.1.1) of rabbit intestinal epithelial cells. One site regulates activation of the catalytic site, while the other site regulates inhibition. A synthetic prostaglandin analogue, 7-oxa-13-prostynoic acid, is recognized at both sites in a concentration-dependent manner. At concentrations of 7-oxa-13-prostynoic acid less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Thus, compounds known to activate adenylate cyclase activity, such as cholera toxin [23] and prostaglandin E , [24] also produced a small but reproducible increase in dome formation. inhibitors of cyclic AMP phosphodiesterase activity [25] , such as theophylline and 1-methyl-3-isobutylxanthine, caused a much more dramatic increase in dome formation.…”
Section: Cyclic Amp As a Positive Regulator Of Dome Formationmentioning
confidence: 96%
“…Thus, compounds known to activate adenylate cyclase activity, such as cholera toxin [23] and prostaglandin E , [24] also produced a small but reproducible increase in dome formation. inhibitors of cyclic AMP phosphodiesterase activity [25] , such as theophylline and 1-methyl-3-isobutylxanthine, caused a much more dramatic increase in dome formation.…”
Section: Cyclic Amp As a Positive Regulator Of Dome Formationmentioning
confidence: 96%
“…Bergström, Carlson & Weeks (1968) and Butcher & Baird (1968) have proposed the concept that prostaglandins may feed back to regulate the adenyl cyclase system. There is evidence for such a mechanism in a variety of tissues (Kuehl, Humes, Tarnoff, Cirillo & Ham, 1970;Sato, Szabo, Kowalski & Burke, 1972;Kantor, Tao & Kiefer, 1974). Kantor et al (1974) identified the presence of two independent prosta¬ glandin receptors on, or associated with, the adenyl cyclase.…”
Section: Effect Of Theophyllinementioning
confidence: 97%
“…There is evidence for such a mechanism in a variety of tissues (Kuehl, Humes, Tarnoff, Cirillo & Ham, 1970;Sato, Szabo, Kowalski & Burke, 1972;Kantor, Tao & Kiefer, 1974). Kantor et al (1974) identified the presence of two independent prosta¬ glandin receptors on, or associated with, the adenyl cyclase. The two receptors appeared to have opposite actions, one regulating the activation of the catalytic site and the other regu¬ lating inhibition.…”
Section: Effect Of Theophyllinementioning
confidence: 97%
“…This difference in propensity for enterotoxin in humans may reflect the absence of factors which participate in the toxin-mediated stimulation of fluid secretion. Prostaglandins have been suggested to play such a role on the basis of their capacity to mimic the effects produced by enterotoxins (6). No correlation, however, between the intestinal levels of these hormones and the propensity for enterotoxic diarrhea has been reported.…”
mentioning
confidence: 99%